Analisis Quality of Service pemanfaatan Ethernet Over IP(EoIP) Tunnel di MikrotikRouterOS dengan Routing Protocol OSPF - Bongga Arif Widodo (Journal of INISTA, 2018)
At present the need for integrated data communication has become a major need for an office, especially at this time it tends to have many branch offices to support its business processes. Problems will arise if the head office has a branch office in a different city. Such as more costs in building network infrastructure to connect between headquarters and branches. One solution is to use Ethernet Over IP (EoIP) Tunnel. That is one of the tunneling features of the Mikrotik that provides an efficient solution to this problem. Network tunnel that is built between Mikrotik devices over TCP / IP. In running EoIP tunnel simulation using IPv4 to communicate with each other. Ethernet Over IP (EoIP) is a proprietary protocol, which is only owned by MikrotikOS. The routing protocol used in the EoIP tunnel is OSPF. Open Shortest Path First (OSPF) is one dynamic routing protocol (Dynamic Routing) that is able to maintain, manage and distribute routing information between networks following any dynamic network changes. Then the quality of service is observed with throughput and packet loss parameters. The results of throughput parameters, the performance of video streaming services reaches 280.45 kbits / Sec. In the video streaming communication service, the average OSPF EoIP Tunnel packet loss reaches 0.92%.